Vigilância intensificada de vírus respiratórios no período pós-pandemia de influenza A(H1N1)pdm09, 2011 a 2013, em Belo Horizonte - Cristiane Campos Monteiro (2015)
Introduction: Acute respiratory diseases account for most of visits and hospitalizations and the etiologic agents involved in these cases are usually viruses and bacteria. In children, viral identification is most common in infants and, in general, viruses are most often found in children under one year. In adults, most infections are bacterial etiology, when viral, influenza is prevalent. The complications caused by influenza are responsible for a significant number of hospitalizations and deaths, especially in children and the elderly. Other viruses such as respiratory syncytial virus, parainfluenza and adenovirus are also often identified as causative agents of acute respiratory infections. It was carried out an intensified surveillance of respiratory viruses with patients admitted to hospital or to emergency room in Belo Horizonte, in 2011. It is known that the monitoring of viral circulation may enhance health surveillance and help to evolve adequate periods and priority groups for vaccination campaigns. The preliminary results of the intensified surveillance program guided its national spread out by the Ministry of Health in Brazil. Objectives: To describe the epidemiological profile of the reported cases with severe acute respiratory syndrome between 2011 and 2013 in the city of Belo Horizonte, Brazil. Methods: This cross-sectional study analyzed data of reported cases with severe acute respiratory syndrome (SARS). The data included in the notification form addressed demographic, epidemiological, and clinical variables. The viruses influenza types A and B, adenovirus, parainfluenza types 1, 2, 3 and RSV were identified by both methods. Results: It was reported 5,158 cases of SARS during the study period. Samples of nasopharyngeal swab was collected for 77% (n=3,974) patients, and 17.3% (n=688) of them was positive for any respiratory virus. Three patients were identified with more than one virus. The age group with the highest number of confirmed cases was children under five years-old, followed by patients 20 to 59 years-old. The hospitals with an Epidemiological Surveillance Unit (ESU) reported more than half of suspected cases (52.4%) and half of the confirmed cases. The influenza A (50.9%) was the most frequent virus found. The subtype (H1N1) pdm09 was identified in greater proportion in the adult population, half of them in the group 20 to 59 years. RSV (35.9%) was the second most isolated respiratory virus, and in children under five years this proportion was 34%. The influenza A (H3N2) was identified in 18.5% of positive samples and other viruses were unrepresentative. The influenza virus circulated every month, and the higher incidence period interposed with the highest activity of RSV. Among the 54 patients infected with respiratory virus who died, 80% had been identified with influenza virus (n = 43), 55.5% of them with subtype A (H1N1) pdm09. Adults of 20 to 59 years accounted for 66.7% of deaths from this subtype. There was no significant statistical difference for sex, postpartum and place of residence compared the confirmed cases and discarded / not collected cases by the chi- square test with 95 % significance level. Conclusion: These findings showed the importance of monitoring the seasonality of respiratory viruses, and the need to adopt specific control measures in a timely manner. Furthermore, it is necessary to expand and to strengthen the epidemiological surveillance in hospital settings, considering it as a partner of the surveillance actions in the city.